Association between the gut microbiotic composition and dietary patterns in hypertensive elderly patients: a cross-sectional study - Hsi-Cheng Hung; Yuan-Yuan Lin; Wan-Jung Tien; Yu-Yoh Chen; Suh-Ching Yang (Nutrition & Metabolism)
Abstract Background Many studies on gut microbiota and hypertension have not focused on detailed dietary intake and eating habits, especially in older adults. This cross-sectional study aimed to examine the gut microbiota profiles of hypertensive elderly individuals in relation to their dietary patterns and nutrient intake. Methods Twenty hypertensive patients and 21 age-matched healthy controls (aged 65–80 years) were recruited from Cathay General Hospital (Taipei, Taiwan). Data collected included anthropometric measurements, blood pressure, blood biochemical analyses, and dietary intake (24-h recall and food frequency questionnaires) and fecal microbiotic composition (via 16S rRNA sequencing). Results Hypertensive patients had significantly higher BMI, waist circumference, and systolic blood pressure. They also showed lower levels of Bacteroides caccae and Barnesiella, and higher levels of Enterobacteriaceae, Enterobacter, Acidaminococcus, and Bacteroides plebeius. Bacteroides caccae abundance was negatively correlated with the intake of saturated fats, sodium, staple foods (e.g., bread, steamed buns, noodles), nut oils, and seasonings. Conclusions Hypertensive patients showed distinct gut microbiota profiles, with lower levels of Bacteroides caccae and Barnesiella, and higher levels of Enterobacteriaceae-related taxa. The abundance of Bacteroides caccae was negatively associated with the intake of saturated fats, sodium, and staple foods, suggesting a link between diet, gut microbiota, and hypertension.